(untitled) (Jurnal Bahasa, 2010)
This research examines the function of prosody in Malay syair, a genre of Malay traditional poetry. Prosody in syair is optimised to convey its message together with emotional meaning. This is due to the poetic licence of the Malay syair, in which structure and form are not subjected to rigid grammar. To prove this assertion, research was conducted using five methods, namely fieldwork, interviews, audio recordings, experimental and data analysis. Fieldwork and data collection were conducted in various locations in Malaysia. These locations were divided into four zones; North, South, East and West; as well as in Sabah and Sarawak. Additional locations in Indonesia were Pekan Baru and Medan and, in Brunei, Bandar Seri Begawan. In each location, all selected informants were asked to recite Malay syair with various types of melody; these recitals were recorded. The resulting audio data were then analysed using the PRAAT programme. The analysis shows the existence of two cases: segmentation of information units and the optimisation of prosodic features in the recital of syair. Keywords: prosody, segmentation, stylisation, information units, pattern